1986
DOI: 10.1161/01.str.17.6.1277
|View full text |Cite
|
Sign up to set email alerts
|

Dolichoectatic basilar artery: a review of 23 cases.

Abstract: SUMMARY The dolichoectatic basilar artery was found in 23 cases during a 10-year period. The 19 males and 4 females ranged in age from 30 to 69 years (mean: 55 years). Hypertension was noted in 17 patients. In seventeen (74%) of the present cases this anomaly could be visualized with CT scan. Seven patients (30%) presented with pontine infarction, which was identified on CT scan in all cases. Vertebro-basilar insufficiency was found in four patients. One patient had transient ischemic attacks. There were facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
2
6

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 20 publications
5
84
2
6
Order By: Relevance
“…One patient demonstrated basilar artery ectasy on CT scan and cerebral angiography, as described by others. 7,8 Female carriers In the 10 female carriers, symptoms were much milder, a finding confirmed by others. 9 None of them suffered from renal failure, severe cardiac disease or had experienced a stroke.…”
Section: Clinical Manifestations Of Male Patientssupporting
confidence: 73%
“…One patient demonstrated basilar artery ectasy on CT scan and cerebral angiography, as described by others. 7,8 Female carriers In the 10 female carriers, symptoms were much milder, a finding confirmed by others. 9 None of them suffered from renal failure, severe cardiac disease or had experienced a stroke.…”
Section: Clinical Manifestations Of Male Patientssupporting
confidence: 73%
“…Hemorrhage, either due to rupture of the vertebrobasilar fusiform aneurysm or as a complication of anticoagulation, was not seen at all in our study; neither was it reported in the series of Yu et al 9 or Nishizaki et al 5 Whenever hemorrhage was seen in those patients, a separate cause, such as concomitant saccular aneurysm, carotid fusiform aneurysm, or uncontrolled hypertension, was evident.…”
contrasting
confidence: 71%
“…Those patients with compressive symptoms went on to develop brainstem ischemia or a progressive mass effect due to the fusiform aneurysm. Nishizaki et al 5 suggested the use of antiplatelet therapy in all patients with vertebrobasilar fusiform aneurysm, even those without ischemic symptoms. No follow-up of their patients is available.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13] However, pathological changes in the arterial wall, consisting primarily in defects in the internal elastic lamina with thinning of the media secondary to smooth muscle atrophy, 14 -16 may predispose patients to intracranial bleeding of various kinds. Knowledge of hemorrhagic stroke as a clinical feature of VBD has come from case reports involving a small number of patients.…”
mentioning
confidence: 99%